Environmental Norm Diffusion Post-USAID Aid in Malang Village: An Ethnographic Review - Najwah, Lia Nihlah; Azis, Aswin Ariyanto; Hari Susilo, Anggun Trisnanto (Department of International Relations, Universitas Brawijaya, 2025)
The foreign aid program through capacity development projects by the United States Agency for International Development (USAID), which addresses water and sanitation issues in Pakis Kembar Village, Malang Regency through the IUWASH program, is perceived as less effective in constructing global environmental norms at the local level. Therefore, this research aims to measure the extent to which the process of constructing and disseminating global environmental norms at the community level has progressed and to identify the current status of norm construction. Employing the norm life-cycle concept, the study will examine how the stages of global environmental norms can be socialized and internalized through norm entrepreneurs in Tegal Pasangan Hamlet, Pakis Kembar Village, Malang Regency. The use of ethnographic methods with thematic ethnographic data analysis techniques is deemed relevant, given that the primary focus of the research is on individual or community behavior, which is closely influenced by local culture and other immaterial aspects such as norms and ideas. Overall, it is evident that there has been no significant change in the habits of the community, thus justifying that the norm cycle process has only reached the norm cascade stage.